The institutional and cultural construction of the third age: shifts and interfaces - Turai Tϋnde (Calitatea Vieții, 2013)
The paper presents the constructions of the old age from the point of view of the elderly. On the macro-level, the division of the life-course and the meanings related to the specific life stages are dominated by the influence of the process of institutionalisation. The formal sector of the social security system codifies the later life, according to impersonal, centrally controlled, structurally definable principles. The cultural category of old age is formed on the micro-level, and its roots are mostly in the inner mechanisms of the ageing and the inside understanding of the elderly population. The paper presents the results of an anthropological study conducted in Romania. Significant shifts seem to exist between the agricultural and the non-agricultural population. The article brings out the complexity of the third age: the analysis presents the principles of the different constructions of old age, their limits, and the interactive relation between them.